2021
DOI: 10.3390/pediatric13030058
|View full text |Cite
|
Sign up to set email alerts
|

Brugada Pattern in a Child with Severe SARS-CoV-2 Related Multisystem Inflammatory Syndrome

Abstract: This report presents the first case of Brugada pattern complicated by a supraventricular arrhythmia in a child with SARS-CoV-2 related Multisystem Inflammatory Syndrome in Children (MIS-C). A 7-year-old boy came to our Emergency Department with 7 days of abdominal pain and fever. MIS-C was diagnosed on the basis of the clinical, laboratory and instrumental tests. On admission, ECG showed type 1 Brugada pattern in the right precordial leads. During hospitalization the onset of supraventricular arrhythmias compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Otherwise, the patient was affected by Sars-CoV-2 during the previous 6 months and his ECGs over this period always showed stable left upper atrial rhythm; there was no availability of previous ECGs prior to the infection. Common cardiac manifestations in SARS-CoV-2 infection and Multisystem Inflammatory Syndrome in Children are ventricular disfunction, coronary anomalies and a wide spectrum of rhythm abnormalities [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, the patient was affected by Sars-CoV-2 during the previous 6 months and his ECGs over this period always showed stable left upper atrial rhythm; there was no availability of previous ECGs prior to the infection. Common cardiac manifestations in SARS-CoV-2 infection and Multisystem Inflammatory Syndrome in Children are ventricular disfunction, coronary anomalies and a wide spectrum of rhythm abnormalities [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The overall incidence of dysrhythmias is 55.1 per 100,000 pediatric ED visits [ 1 ]. Nevertheless, the pediatric ED physician should be able to determine whether child requires immediate examination and referral to a cardiologist [ 2 , 3 ]. Sacchetti et al [ 4 ] conducted a retrospective review of cardiac dysrhythmias in children presenting to the ED, and revealed that sinus tachycardia was the most commonly reported dysrhythmia (50%), followed by supraventricular tachycardia (13%), nonspecific dysrhythmias (10.6%), bradycardia (6%), and atrial fibrillation (4.6%).…”
Section: Introductionmentioning
confidence: 99%
“…He was admitted for 20 days with no recurrence of arrhythmias. 8 Choi et al, described a 19‐year‐old patient, admitted for hypoxemia requiring intubation and fevers who was found on day 3 to be in Brugada pattern. This individual's Brugada pattern resolved by day 10 during hospitalization without recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The patient had Brugada pattern seen on admission ECG and developed atrial ectopic tachycardia during admission requiring synchronized cardioversion followed by pharmacological therapy with sotalol. He was admitted for 20 days with no recurrence of arrhythmias 8 . Choi et al, described a 19‐year‐old patient, admitted for hypoxemia requiring intubation and fevers who was found on day 3 to be in Brugada pattern.…”
Section: Discussionmentioning
confidence: 99%
“…To the Editor: While structural cardiac alterations have been widely investigated, few studies have analyzed electrocardiogram (ECG) abnormalities in multisystem inflammatory syndrome in children (MIS-C) [1][2][3]. We examined cardiac dysfunction and patterns of cardiac rhythm abnormalities in a cohort of 53 MIS-C patients.…”
mentioning
confidence: 99%